Smart Doll - Reem Dalab; Ali Yassin (My University, 2023)
This project presents the development of an innovative interactive doll equipped with a camera and microphone, aiming to strengthen the bond between parents and their children. The doll incorporates cutting-edge technology to facilitate real-time remote monitoring and control through a dedicated website, enabling parents to observe and interact with their child from a different room. The interactive doll offers a two-way communication channel, allowing the child to engage in play while the doll captures their words and repeats them back, fostering a sense of companionship and entertainment. The camera module embedded within the doll provides a live video feed, enabling parents to visually monitor their child's activities in real-time. This project demonstrates the successful integration of hardware components, software development, and web-based communication to create an interactive doll that enhances child-parent interaction. The system's intuitive interface and remote monitoring capabilities make it an ideal tool for busy parents seeking to actively participate in their child's daily activities and provide them with a supportive, interactive playmate.